Politics applications in the Colombian novel La casa de las dos palmas, by the writer Manuel Mejía Vallejo - Sandoval, Liliana Andrea; Sierra, Claudia Marcela (Rastros Rostros, 2011)
This article is based on the research “Political proposals in the Colombian novel of the 20th century” of Universidad Cooperativa de Colombia, Bucaramanga, 2009, which consists of three parts: the triple mimesis of Ricoeur in time and narrative, the analysis of author’s environment and the dissemination of his work in school environments. The novel La Casa de las dos palmas written by Manuel Mejia makes reference to the socio-political reality of this time, the marked machismo and the subjugation of women in Colombia.The novel is worked with ninth grade students in order to motivate them to reading,taking into account theme,objectives, and indicators of achievements, accomplishments and assessment. Students with recycling-material puppets dramatize the work which they have read and analyzed in groups
Keywords: Puppets; Mimesis; Narrative; Novel; Political violence